Can ICT reduce poverty and unemployment and elevate development integrating micro, small, and medium enterprises in Bangladesh? – sharing Asian experiences - Mohammad, Mozammel Haque; Ahlan, Abdul Rahman (2018)
Information and Communication Technology (ICT) can boost the performance of people and improve overall human capital for the alleviation of poverty in a society. Today, ICT is considered as one of the major sources of driving force for the overall economic development integrating with Micro, Small and Medium Enterprises (MSMEs). The e-Commerce has a great role in achieving business performance in the emerging Asian countries. However, MSMEs are experiencing more challenges that prevent them from further increasing their business. The earlier studies question to which extent MSMEs have benefited from these businesses. Therefore, the main purpose of this study is to demonstrate the importance of ICT in developing MSMEs based on the success stories of emerging Asian countries. This study based on subjective/argumentative i.e., idea generation in Information Systems (IS). The findings of the study reveal that the MSMEs utilizing ICT can alleviate poverty and unemployment. It also reveals that MSMEs with ICT and e-Commerce can enhance employment and new job creation that can contribute to the overall economic development. This study is expected to extend for further an empirical investigation broadly on the same issue to validate the research results.